Does fiscal decentralization encourage corruption in local governments? Evidence from Indonesia - Anisah Alfada (Journal of Risk and Financial Management, 2019)
This study examines the effects of fiscal decentralization on corruption by analyzing whether the degree of fiscal decentralization facilitates or mitigates the number of corruption cases in Indonesia's local governments. The research utilizes a panel data model and a system Generalized Method of Moments (GMM) estimator to assess the degree of fiscal decentralization on corruption in 19 provinces for the period between 2004 and 2014. The estimation results reveal that the degree of fiscal decentralization, both expenditure and tax revenue sides, drives a growing number of corruption cases in local governments. A lack of human capital capacity, low transparency and accountability, and a higher dependency on intergovernmental grants from the central government may worsen the adverse effects of corruption. Our results suggest that a more heterogeneous population and higher political stability mitigate the adverse effects of corruption. Furthermore, this is the first corruption study in Indonesia to create corruption measures from the number of corruption cases investigated by the Indonesia Corruption Eradication Commission as well as extensive, provincial-level government financial data. As a result of using these different datasets, this research advances existing empirical studies and makes policy recommendations for the local governments in Indonesia.
Keywords: 330; corruption; fiscal decentralization; Indonesia